THROMKIDplus Patient Registry and Biomaterial Banking for Children with Inherited Platelet Disorders - Ballmaier, Matthias; Germeshausen, Manuela; Schulze, Harald; Andres, Oliver; on behalf of the THROMKIDplus Study Group (Hämostaseologie, 2023)
Inherited platelet disorders (IPDs) represent a heterogeneous group of disorders that include both quantitative (thrombocytopenia or thrombocytosis) and qualitative (thrombocytopathy) defects. To gain better knowledge about the prevalence, pathogenesis, and clinical consequences of specific diseases, to improve diagnosis and treatment of patients with IPD, and to support translational research on a genetic, molecular, and physiological basis, the THROMKIDplus study group currently comprising 24 sites in Germany, Austria, and Switzerland decided to establish a patient registry with associated biomaterial banking for children. This registry is designed as a retrospective-prospective, multicenter observational study and supposed to launch in the second half of 2023. Blood smears, plasma, platelet pellets, and DNA of patients will be stored in certified biomaterial banks for future translational research projects. The main inclusion criteria are (1) diagnosis of or highly suspected IPD after assessment of a THROMKIDplus competence center and (2) patients aged 0 to 17 years. Initial and follow-up data on patient history, laboratory parameters, standardized documentation of bleeding tendency, and congenital defects are collected according to good clinical practice and current data protection acts by using the MARVIN platform, a broadly used data management system supported by the German Society for Pediatric Oncology Hematology (GPOH). The THROMKIDplus study group intends to enroll ∼200 patients retrospectively and an annual amount of ∼50 patients prospectively.
Keywords: inherited platelet disorder; patient registry; biomaterial banking